G135(P) A novel approach to NICE audit?. (7th April 2014) - Toal, G; Nathan, D
Abstract : Aims: Evaluation of the assessment of autistic spectrum disorder. Methods: We appraised our current assessment for autistic spectrum disorder using process audit . This traffic light system, used in business models, highlights areas of good practice, and grades areas requiring marked or moderate improvement. A process audit examines the resources (time, materials and people) used to transform inputs into outputs, encompasses the environment, methods (procedures and instructions) followed and the measures collected to determine process performance. A process audit checks the adequacy and effectiveness of the process controls established by guidelines, work instructions, flowcharts, training and process specifications. This system is successfully applied in Industry. Using best practice outside Medicine, we adapted it into a prospective NICE audit reviewing the assessment of Autistic Spectrum Disorder in an urban deprived population. A parent/child questionnaire was derived from NICE audit criteria and piloted. This aimed to capture patient views to cross reference their perspectives against NICE standards for this process audit. It allowed a holistic approach to the audit. Results: The audit identified service provision strengths and gaps compared to NICE recommendations, while reinforcing areas of importance to parents/children. Managing all NICE expectations within clinical consultations which consist of a through physical health review, developmental assessment, mental health screening for co-morbidity and child protection assessment (bruising) demands sufficient time and staff competencies. This time commitment is not reflected in the tariff for clinical funding. Problems will become more challenging given decreasing resources, both in terms of emotional health support/screening for children following attrition of the clinical skill base for mental health and in terms of time allocated to ASD assessments in community paediatric clinics. Conclusion: Issues raised in this audit will require adaptations within the control of clinicians but also suggested areas for discussion with commissioners as it highlighted gaps that required broader agreement for improvement. Effective process audit requires a holistic approach to clinical practice and demands ongoing dynamic process evaluation. Process audit is a useful method and can be generically applied to other NICE audits.